Dynamics of retail-bank branching in Antwerp (Belgium) 1991–2006: Evidence from micro-geographic data - Huysentruyt, Marieke; Lefevere, Eva; Menon, Carlo (Journal of Banking & Finance, 2013)
We exploit a comprehensive new panel dataset on retailbank branch locations in 233 neighborhoods (local markets) in the metropolitan area of Antwerp to describe (i) how between 1991 and 2006 the patterns of bank presence, entry, exit and choice deeply evolve and (ii) whether and how changes in these “on the ground” patterns systematically diverge across Antwerp’s different, highly segregated neighborhoods. We show that over the 15-year period under study entry and exit dynamics substantially intensify, the level change in branch desert grows significantly, and bank choice markedly declines; and that between 1996 and 2001, these changes are robustly associated with the neighborhood average income. In doing so, we advance a new technique for generating spatial measures that both minimize the discretization bias and can be reliably linked to neighborhoods. We demonstrate that the resulting measures are indeed more precise than traditional count measures.